Sequential exploration of strategies and challenges in implementing culturally responsive pedagogy - Genalyn Panganiban-Lualhati; Teodoro B. Panganiban (Institute of Advanced Engineering and Science, 2026)
The implementation of culturally responsive pedagogy (CRP) in higher education is essential for fostering inclusive and equitable learning environments. However, faculty members often face challenges such as addressing biases and ensuring inclusivity. This study examines the strategies and challenges of CRP implementation at a state university in the Philippines using an exploratory sequential mixed methods approach. The qualitative phase involves in-depth interviews with 10 faculty members to identify key CRP strategies and challenges. The quantitative phase surveys 116 faculty members to assess the effectiveness of these strategies and measure the difficulty of encountered challenges. Thematic analysis and descriptive statistics provide a comprehensive understanding of CRP implementation. Findings reveal that CRP enhances student engagement and learning outcomes but is hindered by challenges related to bias, institutional support, and creating inclusive environments. The study calls for professional development programs and policy reforms to help faculty adopt culturally responsive teaching (CRT) and gain stronger institutional support. It also highlights the need for collaboration among educators, administrators, and policymakers to ensure CRP is effectively and sustainably implemented.